Is there a commitment in trainee teachers of Israel's Arab sector to educate for multiculturalism?. Issue 3 (4th May 2021) - Abbas, Randa; Ilaiyan, Salman
ABSTRACT: This research discusses the instruction of multiculturalism in Arab-Israeli teacher training colleges and seeks to discover whether its trainees are committed to educate for multiculturalism. It is a pioneering project as it inquiries how Arab students at departments of teacher education in Israeli Colleges learn about multiculturalism. On the theoretical level, the study contributes to the understanding of multicultural research. On the practical level, it provides help in preparing students as multiculturally tolerant teachers equipped with the tools needed for educating for pluralism and social tolerance.